Parent Involvement : Form of Society Participation with Madrasah - Abdul Ghafur; Suhaimi Panecekak (EDUCARE: Jurnal Ilmu Pendidikan, 2023)
This study aims to examine the forms of parental involvement as a manifestation of community participation in early childhood education. The research addresses the urgent need to strengthen collaboration between schools and families to enhance the quality of children's education, particularly in madrasah environments. A descriptive qualitative method was employed, involving observations, document reviews, and in-depth interviews with school leaders, teachers, and four parents. Data analysis followed the flow model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The findings indicate that parental involvement manifests in four key dimensions: parenting, communication, volunteering, and home-based learning. These dimensions align with Epstein’s framework and are reflected in activities such as parenting workshops, digital communication via WhatsApp groups, volunteering in school events, and parental support in children’s home learning. The implications of this study underscore the importance of institutionalizing parental roles through structured programs and open communication strategies, which are vital in fostering sustainable and mutually beneficial school-community partnerships. Moreover, the research offers a practical model for other educational institutions to adopt similar participatory frameworks in nurturing inclusive and supportive learning environments.